CO2 and summer insolation as drivers for the Mid-Pleistocene Transition - M. D. W. Scherrenberg; M. D. W. Scherrenberg; C. J. Berends; R. S. W. van de Wal; R. S. W. van de Wal (Climate of the Past)
During the Mid-Pleistocene Transition (MPT; ∼ 1.2–0.8 Myr ago) the dominant periodicity of glacial cycles increased from 41 kyr to an average of 100 kyr, without any appreciable change in the orbital pacing. As the MPT is not a linear response to orbital forcing, it must have resulted from feedback processes in the Earth system. However, the precise mechanisms underlying the transition are still under debate.